Reduced Insulin-Like Growth Factor 1 Is Associated with Insulin Resistance in Obese Prepubertal Boys - Kuang, Jiangying; Zhang, Li; Xu, Yueqin; Xue, Jiang; Liang, Shuang; Xiao, Juan (BioMed research international, 2021)
As one of the most common features of obesity, insulin resistance is central to the pathogenesis of the metabolic syndrome. Low insulin-like growth factor 1 (IGF-1) levels have been proven to be associated with many traditional cardiovascular risk factors, but it still remains controversial with the relationship between IGF-1 and insulin resistance. Accordingly, the main purpose of this study is to investigate the relationship between IGF-1 and insulin resistance in obese prepubertal boys. We used the whole-body insulin sensitivity index (WBISI) to represent insulin resistance. 70 obese prepubertal boys were included in the study, and the obese subjects were divided into two groups by using 1.285 as a threshold value for WBISI. Clinical examination and laboratory examinations were assessed for all participants. Among obese boys, the group of children with WBISI≤1.285 had lower IGF-1 standard deviation scores (SDS) (p=0.021) than the WBISI>1.285 group. The results of multiple linear analyses show that lg WBISI was positively correlated with IGF-1 SDS (p=0.031) after adjusting for traditional cardiovascular risk factors. IGF-1 SDS was negatively associated with insulin resistance in obese prepubertal boys, independent of other traditional cardiovascular disease risk markers.